THE EFFECT OF WORK FLEXIBILITY, COMPENSATION, WORKLOAD AND JOB SATISFACTION ON GOJEK DRIVER PERFORMANCE IN NORTH BEKASI - Ivani Rahmawati; Muhammad Richo Rianto; Eri Bukhari (Draf Solusi Indonesia, 2023)
This study is motivated by the results of pre-research on Gojek application users regarding the performance of Gojek drivers which shows that the performance is very good. Therefore, this study aims to measure and analyze whether there is an influence between work flexibility, compensation, workload and job satisfaction on the performance of Gojek drivers in North Bekasi. The results of this study indicate that the Job Flexibility variable has no effect on the performance of Gojek drivers. Whether The Compensation, Workload and Job Satisfaction variables have an effect on the performance of Gojek drivers